2021
DOI: 10.1039/d1ee01265g
|View full text |Cite
|
Sign up to set email alerts
|

Stabilizing electrode–electrolyte interfaces to realize high-voltage Li||LiCoO2 batteries by a sulfonamide-based electrolyte

Abstract: A sulfonamide-based electrolyte can greatly improve the cycling stability of the commercial LiCoO2 cathode at high cut-off voltages in Li metal||LCO batteries by stabilizing the electrode–electrolyte interfaces on both the anode and cathode.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
92
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 119 publications
(94 citation statements)
references
References 61 publications
2
92
0
Order By: Relevance
“…[ 43 ] It is also well known that the organic electrolytes are usually susceptible to decompose especially when the voltage approaching 4.6 V, which exceeds the working window of many solvents used in the electrolyte. [ 44,45 ] For example, ethylene carbonate itself is considered to be stable only under a voltage of 4.4 V. [ 46 ]…”
Section: Challenges Of Lco For Achieving a Higher Energy Densitymentioning
confidence: 99%
See 4 more Smart Citations
“…[ 43 ] It is also well known that the organic electrolytes are usually susceptible to decompose especially when the voltage approaching 4.6 V, which exceeds the working window of many solvents used in the electrolyte. [ 44,45 ] For example, ethylene carbonate itself is considered to be stable only under a voltage of 4.4 V. [ 46 ]…”
Section: Challenges Of Lco For Achieving a Higher Energy Densitymentioning
confidence: 99%
“…Besides dominant strategies of bulk doping and surface modification, the development of highly compatible electrolytes to form stable CEI is also an important method to protect LCO in high voltage. The recent research results have shown that sulfonamide‐based electrolyte [ 44 ] and modified electrolyte with nitriles can effectively [ 71 ] improve the cycle stability of HV‐LCO. Therefore, design electrolytes and additives to form a stable CEI layer and additionally suppress the side reactions of LCO‐based LIBs is also one of the key and tough hotspots in the current research of HV‐LCO.…”
Section: Challenges Of Lco For Achieving a Higher Energy Densitymentioning
confidence: 99%
See 3 more Smart Citations